ANALISIS RESEPSI TERHADAP FILM DOKUMENTER “DANAU BEGANTUNG” DI LANSKAP KATINGAN-KAHAYAN - Ayu Lestari, Mega; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Previously, Central Kalimantan Province had experienced the worst of forest fire which destructed a huge amount of forest and peatland. Including at Pulang Pisau District, landscape of Katingan-Kahayan, the surrounding ecosystem on Begantung Lake had also been degraded since recent years ago. However, sectoral ego and overlapping regulations have deteriorated the condition of forests; in which affected to peatland and lake-dependent communities at Tanjung Pusaka Village, where lives of indigenous norms and value, and its biodiversity were being threatened. By using method of reception analysis, this research described how the interpretation of local citizens toward documentary film “Danau Begantung”. Then, these results showed in which: 1) they understood the local wisdom as a new lesson-learned and it got them interested to experience Lake Begantung; 2) the major actor within this film was acknowledged as an actor that can communicate well; 3) this film was perceived as important and relevant amid local issues; and 4) local citizens’ interpretations were cathegorized into positions’ model explained by Stuart Hall, such as dominant-hegemonic reading, negotiated reading, and oppositional reading. Therefore, reception analysis was conducted to help understand the process of local citizens’ interpretation toward documentary film Danau Begantung. It needs to engage local community and its socio-historical contexts, then to fill the social gap within local wisdom between other communities and government in general, so that Danau Begantung film could be more effective as an advocacy tool